2018
DOI: 10.1111/eva.12603
|View full text |Cite
|
Sign up to set email alerts
|

Genomic sequence and copy number evolution during hybrid crop development in sunflowers

Abstract: Hybrid crops, an important part of modern agriculture, rely on the development of male and female heterotic gene pools. In sunflowers, heterotic gene pools were developed through the use of crop‐wild relatives to produce cytoplasmic male sterile female and branching, fertility restoring male lines. Here, we use genomic data from a diversity panel of male, female, and open‐pollinated lines to explore the genetic changes brought during modern improvement. We find the male lines have diverged most from their open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 40 publications
1
29
0
1
Order By: Relevance
“…The call set included the 1518 samples described above, the Sunflower Association Mapping (SAM) population (a set of cultivated H. annuus lines 54 ), and wild Helianthus samples previously sequenced for other projects [54][55][56] , for a total of 2392 samples (Supplementary Table 1). The additional samples were included to improve SNP calling, and to identify haploblock genotypes.…”
Section: Variant Callingmentioning
confidence: 99%
“…The call set included the 1518 samples described above, the Sunflower Association Mapping (SAM) population (a set of cultivated H. annuus lines 54 ), and wild Helianthus samples previously sequenced for other projects [54][55][56] , for a total of 2392 samples (Supplementary Table 1). The additional samples were included to improve SNP calling, and to identify haploblock genotypes.…”
Section: Variant Callingmentioning
confidence: 99%
“…The hybrid system based on a CMS commonly comprises of a three-line system: the male sterile genotype (A line), which is maintained by maintainer (B line) usually with a fertile cytoplasm, and a restorer (R line) for restoring the male fertility in hybrids via dominant fertility restorer genes [8,13]. Earlier efforts of sunflower breeders using this system have resulted in the significant increase of the production and quality [14,15]. Drought is among the biggest crop production challenges of the 21st century and sunflower is not an exception to drought stress [16].…”
Section: Introductionmentioning
confidence: 99%
“…The third section concerns introgression between wild and domestic populations (Owens, Baute, Hubner, & Rieseberg, ; Schreiber, Himmelbach, Börner, & Mascher, ; Taitano et al., ; Vigueira et al., ). The first of these studies authored by Vigueira et al.…”
mentioning
confidence: 99%
“…In sunflower, Owens et al. () analyze a late phase in domestication, hybrid crop development, which involved widespread introgression from wild relatives as populations were partitioned into male and female lines. Further, they showed that there was minimal selection for overdominance, but that selection was centered around branching and fertility/sterility mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation